2023
DOI: 10.3390/nano13081324
|View full text |Cite
|
Sign up to set email alerts
|

The Process and Mechanism of Preparing Nanoporous Silicon: Helium Ion Implantation

Abstract: Ion implantation is an effective way to control performance in semiconductor technology. In this paper, the fabrication of 1~5 nm porous silicon by helium ion implantation was systemically studied, and the growth mechanism and regulation mechanism of helium bubbles in monocrystalline silicon at low temperatures were revealed. In this work, 100 keV He ions (1~7.5 × 1016 ions/cm2) were implanted into monocrystalline silicon at 115 °C~220 °C. There were three distinct stages in the growth of helium bubbles, showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For effective drug delivery, the introduction of mediators such as drug carriers and hydrogels or physical methods such as creating micropores on a material surface have been investigated [5][6][7][8]. In particular, to store and deliver drugs, it has been reported that micropores can be formed on the material surface using laser-based physical surface modification methods such as ion beam and femtosecond laser irradiation or chemical surface modification methods such as anodic oxidation and polishing [9][10][11][12]. However, physical methods such as laser irradiation have limitations such as variations in the irradiation conditions for each material property, slow processing speed, and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…For effective drug delivery, the introduction of mediators such as drug carriers and hydrogels or physical methods such as creating micropores on a material surface have been investigated [5][6][7][8]. In particular, to store and deliver drugs, it has been reported that micropores can be formed on the material surface using laser-based physical surface modification methods such as ion beam and femtosecond laser irradiation or chemical surface modification methods such as anodic oxidation and polishing [9][10][11][12]. However, physical methods such as laser irradiation have limitations such as variations in the irradiation conditions for each material property, slow processing speed, and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the methods mentioned above, the ion implantation process [15,16] is a relatively mature technology for synthesizing NPs with abundant advantages such as the uniformity of produced NPs. The ion implantation method can achieve large-scale material modification through simple operations, forming new doping systems and obtaining excellent device performance.…”
Section: Introductionmentioning
confidence: 99%